Academic Discipline «Fundamentals of Student Learning (Self-Management of Learning)» as a Tool for Developing Educational Autonomy of Students of Vocational and Higher Education Institutions - Kushchenko, Iryna; Bazylenko, Anastasia (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article highlights the essence of the academic discipline “Fundamentals of Student Learning (Self-Management of Learning)” as an effective tool for developing the educational autonomy of students in institutions of professional pre-higher and higher education. The purpose of the study is to highlight the pedagogical potential of the specified discipline as a factor in the formation of students' educational autonomy, as well as to determine the conditions, methods and practices for its successful implementation in the educational process of the University “Ukraine”. The following methods were used during the study: analysis and generalization of scientific and pedagogical literature, content analysis of educational documentation, a survey (questionnaire of students), and methods of descriptive statistics for interpreting the results obtained. The article focuses on the key components of educational autonomy, in particular, the development of skills of reflection, critical thinking, self-organization, time management, the ability to set goals, planning, and self-control. Pedagogical conditions that ensure the effectiveness of course implementation are identified: orientation towards student-centered learning, integration of digital technologies, implementation of reflective practices, and the use of self-study strategies. The results obtained indicate a positive impact of the discipline on students' motivation, the formation of a responsible attitude towards the educational process, increased involvement in educational activities, and readiness for continuous professional growth. Educational autonomy should be understood as the student's ability and readiness to independently determine educational goals, plan, organize, control, and evaluate their own educational activities, based on awareness of personal needs, motivation for self-study, and the ability to self-reflect. The conclusions emphasize that the development of educational autonomy is a necessary condition for training a competitive specialist capable of self-study, flexible response to the challenges of modernity, and active participation in the knowledge society.